Acoustical Properties of Oxalic Acid-Tartaric Acid-Water Solutions - Upadhyay, G.S.; R. Singh, (Late); Prasad, J.; Singh, H. (Asian Journal of Chemistry, 2010)
The paper reports the acoustical properties of multi component solutions (oxalic acid-tartaric acid-citric acid-water) at 40ºC. The ultrasonic velocities of solutions have been measured and the values of ultrasonic velocity have been utilized to calculate other acoustical parameters such as the adiabatic compressibility, acoustic impedance, apparent molar compressibility, molar sound velocity and molar sound compressibility. The ultrasonic velocities of solutions increase with the increase in the concentration of its any individual component.